Exploring Differences in Household Debt Across Euro Area Countries and the United States - Dimitris Christelis; Michael Ehrmann; Dimitris Georgarakos (Bank of Canada, 2015)
We use internationally comparable household-level data for ten euro area economies and the United States to investigate cross-country differences in debt holdings and the potential of debt overhang. U.S. households have the highest prevalence of both collateralized and non-collateralized debt, hold comparatively large amounts of loans outstanding, and face a higher debt-service burden. These differences are mainly attributed to the U.S. economic environment, which appears to be more conducive to both types of debt. For instance, differences in the economic environment between the United States and the median European country explain more than 85% of the overall difference in the prevalence of debt holdings. Even though U.S. households have higher income and financial wealth than their European counterparts, their debt burden remains comparatively elevated, primarily because a given level of collateral translates into a higher prevalence of collateralized debt, and larger amounts of it, in the United States. This suggests that U.S. households are relatively more vulnerable to adverse shocks.
Keywords: D12; E21; G11; 330; Credit and credit aggregates; Econometric and statistical methods; International topics